Non-spficif forms: Sergio Blanco’s "La ira de Narciso" - Campos Atienzo, Daniela Rebeca (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
In this paper I will analyze how in the piece La ira de Narciso (2016) by the Franco-Uruguayan writer Sergio Blanco there is a theatrical construction structured from the narrative and from the presence of the Brechtian theater as part of those unspecific forms (Pedrosa et al., 2018) the contemporary, thought from the self-fiction and that bifurcation of criticism and theory within the same piece, of the author’s life, with the life of the character and death, that is, of that intersection between the gesture and the deletions that the text presents as a draft, configuring a performative text (Kingler, 2008) in its structural and thematic hybridity, unfolding between the new aesthetics and the literary reinvention linked to the convulsive times of excess visibility and spectacularizing of the private.